2019
DOI: 10.1016/j.neubiorev.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Momentary lapse of control: A cognitive continuum approach to understanding and mitigating perseveration in human error

Abstract: Everyday complex and stressful real-life situations can overwhelm the human brain to an extent that the person is no longer able to accurately evaluate the situation and persists in irrational actions or strategies. Safety analyses reveal that such perseverative behavior is exhibited by operators in many critical domains, which can lead to potentially fatal incidents. There are neuroimaging evidences of changes in healthy brain functioning when engaged in non-adaptive behaviors that are akin to executive defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 141 publications
3
41
0
Order By: Relevance
“…It has been demonstrated that individuals with greater information processing capacity (i.e., higher working memory span) exhibit superior ability with respect to divided and sustained attention (Colflesh and Conway, 2007;Unsworth and Engle, 2007), and therefore, should be less susceptible to the effects of inattention during the performance of demanding tasks. However, this hypothesis is contradicted by the absence of any correlation between individual differences in processing capacity and the occurrence of inattentional blindness (Bredemeier and Simons, 2012;Beanland and Chan, 2016;Kreitz et al, 2016a) or deafness (Kreitz et al, 2016b;Dehais et al, 2019).…”
Section: Toward a Limit Of The Theory Of Limited Resourcesmentioning
confidence: 98%
See 4 more Smart Citations
“…It has been demonstrated that individuals with greater information processing capacity (i.e., higher working memory span) exhibit superior ability with respect to divided and sustained attention (Colflesh and Conway, 2007;Unsworth and Engle, 2007), and therefore, should be less susceptible to the effects of inattention during the performance of demanding tasks. However, this hypothesis is contradicted by the absence of any correlation between individual differences in processing capacity and the occurrence of inattentional blindness (Bredemeier and Simons, 2012;Beanland and Chan, 2016;Kreitz et al, 2016a) or deafness (Kreitz et al, 2016b;Dehais et al, 2019).…”
Section: Toward a Limit Of The Theory Of Limited Resourcesmentioning
confidence: 98%
“…Similarly, the occurrence of stressful and unexpected operational scenarios is known to impair executive functioning and provoke perseveration, see Dehais et al (2019) for review. Perseveration is defined as a tendency to continue an action after cessation of the original stimulation, which is no longer relevant to the goal at hand (Sandson and Albert, 1984).…”
Section: Toward a Limit Of The Theory Of Limited Resourcesmentioning
confidence: 99%
See 3 more Smart Citations